Understanding the digital capabilities of rural communities in low literacy rate areas in Malaysia towards digital society - Samsuddin, Samsul Farid; Mohamed, Nor Aini; Bolong, Jusang (Human Resource Management Academic Research Society, 2021)
Despite several activities been focusing on urban areas, rural areas are no exception in being a digital society. Since the year 2000, various initiatives such as rural libraries establishment and Universal Service Provision (USP) programs tend to narrow down the digital divide between rural and urban areas in Malaysia. However, few empirical studies have been carried out on information access and usage of digital technologies among rural communities in Malaysia. The purpose of this paper is to investigate the digital capabilities of rural communities in low literacy rate areas in Malaysia towards a digital society. This study is a quantitative method and descriptive kind of study using questionnaires as an instrument to collect the data. Multi-stage clusters and simple random sampling were employed and 400 respondents were selected. Analysis performed confirms that rural communities in Malaysia, are digitally connected and informed society (Digital Society). Smartphones and the Internet were the highest types of ICT tools used by the rural communities in the study. The result did reflect on the ownership of their ICT tools, which most of the rural communities afford to have their own smartphones regardless of the level of age. A better understanding of digital capabilities towards information access and usage of digital technologies among rural communities could produce a better understanding of the adoption and usage of digital technologies. The findings are also expected to provide useful inputs in ensuring that the advancements in communications infrastructure and services contribute to the inclusion and participation of all segments of the population in the realization of a Digital Society. Meanwhile, able to understand the human and social factors, which affect and contribute to the adoption and usage of digital technologies and services. Keywords: Digital Society, Digital Capabilities, Information Access, Usage of Digital Technologies,